Low-dose alcohol: Interoceptive and molecular effects, and the role of dentate gyrus in rats. - Randall, Patrick A. (Addict Biol, 2020)
Alcohol abuse and dependence are world-wide health problems. Most research on alcohol use focuses on the consequences of moderate to high levels of alcohol. However, even at low concentrations, alcohol is capable of producing effects in the brain that can ultimately affect behavior. The current studies seek to understand the effects of low-dose alcohol (blood alcohol levels of ≤10 mM). To do so, these experiments utilize a combination of behavioral and molecular techniques to 1) assess the ability of the interoceptive effects of a low dose of alcohol to gain control over goal-tracking behavior in a Pavlovian discrimination task, 2) determine brain regional differences in cellular activity via expression of immediate early genes (IEGs), and 3) assess the role of the dentate gyrus in modulating sensitivity to the interoceptive effects of a low dose of alcohol. Here, we show that intragastric administration of a dose of 0.8 g/kg alcohol produces blood alcohol levels ≤10 mM in both male and female Long-Evans rats and can readily be trained as a Pavlovian interoceptive drug cue. In rats trained on this procedure, this dose of alcohol also modulates expression of the IEGs c-Fos and Arc in brain regions known to modulate expression of alcohol interoceptive effects. Finally, pharmacological inactivation of the dentate gyrus with GABA agonists baclofen and muscimol disrupted the ability of a low dose of alcohol to serve as an interoceptive cue. Together these findings demonstrate behavioral and molecular consequences of low-dose alcohol.